Perancangan Interior Galeri Seni Kontemporer Karya Penyandang Difabel dengan Konsep Universal Design di Surabaya - Clarissa Stefanni; Sherly de Yong; David Tan Kayogi (Intra, 2019)
People with different abilities are often considered unequal and therefore do not have the same rights so they have always been marginalized in various aspects of people's lives. In the context of the arts, non-disable people only see the works of disabled based on compassion without constructive criticism. The mayor of Surabaya, Mrs. Tri Rismaharini committed to provide spaces for art performers centered at Hi-Tech Mall Surabaya. The design of this contemporary art gallery by people with disabilities is a form to fulfill the rights of the disables and at the same time responding to one of Mrs.Risma's hope. The gallery, which has the main function as a communication tool between artists with collectors and the community, is considered as the right place to show the artistic talents of people with disabilities to get proper appreciation, especially from those who are non-disabled. In the design, the method used is Design Thinking which consists of 3 main stages, Understand, Explore, and Materialize. The concept of the design is a public facility that can accommodate the development of diffable artworks with 3 main focuses, Experience, Educate and Appreciate. Gallery design as a public facility should prioritize accessibility aspects for various users so that universal design principles are applied with all considerations in design.